Übersetzung : ein internationales Handbuch zur Übersetzungsforschung. - Kittel, Harald; Frank, Armin Paul, 1935-; Greiner, Norbert, 1948-; Hermans, Theo, 1948-; Koller, Werner, 1942-; Lambert, José; Paul, Fritz, 1942- (Handbücher zur Sprach- und Kommunikationswissenschaft,, 2011)
This international encyclopedia documents and surveys, for the first time, the entire complex of translation as well as the operations and phenomena associated with it. Structured along systematic, historical and geographic lines, it offers a comprehensive and critical account of the current state of knowledge and of international research. The Encyclopedia (1) offers an overview of the different types and branches of translation studies; (2) covers translation phenomena - including the entire range of interlingual, intralingual, and intersemiotic transfer and transformation - in their social, material, linguistic, intellectual, and cultural diversity from diachronic, synchronic, and systematic perspectives, (3) documents and elucidates the most important results of the study of translation to the present day, as well as the current debates, taking into account theoretical assumptions and methodological implications; (4) identifies, where possible, lacunae in existing research, listing priorities and desiderata for further research. The languages of publication are German, English, and French.